Práticas políticas repressivas do Século XX e consciência histórica: um propositivo didático das aulas de História no Colégio Santa Cruz – Araguaína – TO - Coimbra, Kamila Soares de Araújo (Universidade Federal do Tocantins, 2020)
This work presents as an object of research the development of historical consciousness through film didactics. We use the theorization of Jörn Rusen, who understands the application of art as an important element for the development of historical consciousness. The historical clipping was evidenced in two film works: The girl who stole books and The year my parents went on vacation. They are works that include repressive practices in authoritarian regimes, Nazism in Germany and the military regime in Brazil, respectively. The methodology adopted in the research was participant research, in which the empirical object of knowledge was constructed with those surveyed during the course of the study.